The impact of job and communication satisfaction on the financial performance of a mid-sized company - Jelena Rajković; Edit Terek; Maésa Magzan; Dragica Ivin; Milan Nikolić (Journal of Contemporary Economic and Business Issues, 2018)
The paper presents a research on employees' job and communication satisfaction, as well as on financial performances on the example of a mid-sized Serbian company. The company operates in the field of food industry. The research was carried out by means of standardized questionnaires and the examinees werre employed in the observed company. In addition, the impact of job and communication satisfaction dimensions on the items of financial performance was studied as well. The research results showed that the examined employees were generally satisfied with their job and communication, while the financial performances of their company were considered as average. Further, both the dimensions of job satisfaction and communication satisfaction have a significant impact on financial performance items. Their salary, possibilities for promotion, a good organization of meetings, efficient and clear guidelines and meetings, and access to information about the organization as a whole can raise the level of financial performance. On the other hand, the dimensions of job and communication satisfaction do not have a bigger impact on some extreme components of financial performance such as sale growth, competitiveness and growth of the fixed assets in a company.
Keywords: D23; J28; 330; job satisfaction; communication satisfaction; financial performance; Serbia